Evaluation of Optimum Tilt Angles for BIPV Installation in Indonesia - Susan, Susan (Universitas Ciputra Surabaya, 2025)
Generale rules of thumb for PV-tilt in certain area is equal to the latitude angle of the area. Following the rule, PV system on low-latitude area such as Indonesia should be installed in low PV-tilt angle to receive optimum irradiance. Furthermore, installing PV in low tilt angle has many advantages such as reducing the inter-row spacing requirements, increasing the coverage ratio and power density, increasing more PV numbers in lesser area, generating low-cost PV electricity that resulting in higher economy savings. However, installing PV in low tilt angle has also disadvantages such as dust deposition that resulting in less energy efficiency. Furthermore, for roof integrated photovoltaic in the tropics, pitched roof design in certain angles is preferable to response to high precipitation and to reduce minimum indoor room temperature. Therefore, this study aims to evaluate the performance of several PV-tilt design options and identify the optimum tilt angle of horizontal integrated PV based on annual irradiance received and monthly energy fluctuation, particularly in Indonesia. Simulation method is used to generate the number of annual irradiances for several selected sites in Indonesia. Setting on 10° to 30° PV-tilt angle seems to be a good design option based on annual irradiance and percentages of energy fluctuation.